PENYUSUNAN DAN PENGEMBANGAN KURIKULUM ANTITERORISME DI SEKOLAH DAN PONDOK PESANTREN - Andika Hendra Mustaqim (Cakrawala - Jurnal Humaniora, 2010)
Nowadays, educators, parents, and government have been faced by the new problem and it’s very dangerous. What is it? It is a terrorism. If this problen can be solved by immediately, so the Indonesian future will face dark age. Education institution must responsible with terrorisme problem. Not onlythe government, but every elements such as religion and social organizaion.The soul of education in Indonesia is curriculum. Curriculum is the center of education system. If the curriculum is band so education system can not be maximum on the process, and finally the output of education can not be responsible. This soul is run by physic and mind. The physic of education is student, and the the mind is teacher. If three elements support each other and having good sinergy, so it will create the comprehensive  education.In the case of terrorism problem, the element which has significant touch is government. Although terrorism is the common enemy for all Indonesian society. For prevent terrorism, governement or the other elements need help from education sector. The soul of education is curriculum. So there are any development and creation of antiterrorism curriculum.The famous book which written by Robert S Zais, “Curriculum Principles and Foundations”, he classified eight models for developing the curriculum. Zais in Sukmadinata (1997); Subandijah (1993: page 70-75); and Akhmad (1997: page 50-51), these model are adminstrative model, bottom up, demonstration, Beauchamp, Hilda Taba, Interpersonal relationship by Rogers, Systematic Actions Research, and Technology. Keywords: Curriculum, antiterrorism, schools, boading schools